Regulatory medical writing in Switzerland. (1st June 2013) - Billiones, Raquel
Abstract : Switzerland is practically unknown in the drug/medical device regulatory landscape despite being home to some of the world's biggest pharmaceutical firms. This article briefly describes the regulations governing clinical trials in Switzerland and cites examples of Swiss-specific regulatory documents.